Nrf2 Activation Inhibits Effects of Thrombin in Human Amnion Cells and Thrombin-Induced Preterm Birth in Mice - Chigusa, Yoshitsugu (J Clin Endocrinol Metab, 2016)
CONTEXT: Nrf2 is a key transcription factor that modulates cell defense mechanisms against endogenous and exogenous stress. Previously, we reported that thrombin increased matrix metalloproteinases and prostaglandin synthesis in human amnion mesenchymal cells. OBJECTIVE: We sought to determine whether activation of Nrf2 alters the effect of thrombin on prostaglandin synthesis, protease activation, and cytokine release in human amnion. Furthermore, we analyzed the effect of Nrf2 activation on thrombin-induced preterm labor in mice. DESIGN: Primary human amnion mesenchymal cells and pregnant mice were employed to investigate the effect of Nrf2 on thrombin-induced inflammation and preterm birth. SETTING: This was a laboratory-based study using cells and mice. RESULTS: As expected, thrombin increased cyclooxygenase-2, IL-1β, IL-6, IL-8, and matrix metalloproteinase-1 in amnion mesenchymal cells. Preincubation with Nrf2 activators, diethyl maleate or 15-deoxy-Δ12, 14-prostaglandin J2 (15d-PGJ2), profoundly repressed thrombin-induced gene expression. In addition, Nrf2 activation inhibited thrombin-induced cyclooxygenase-2 protein levels and secretion of prostaglandin E2, IL-1β, IL-6, IL-8, TNFα, and granulocyte-macrophage colony-stimulating factor in the media. Whereas vehicle and 15d-PGJ2 did not alter gestational length, all pregnant mice treated with thrombin delivered preterm. 15d-PGJ2 delayed thrombin-induced preterm birth significantly. CONCLUSIONS: The results indicate that Nrf2 activation represents a key stress response in amnion mesenchyme cells and in pregnant mice to mitigate the adverse proinflammatory effects of thrombin on the fetal membranes. We suggest, therefore, that pharmacological activation of Nrf2 may prevent the increased risk of preterm premature rupture of the membranes associated with thrombin activation that accompanies subchorionic hemorrhage or bleeding during pregnancy.